2012
DOI: 10.1136/bjsports-2012-091366
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular structure and function in hypertrophic cardiomyopathy

Abstract: Background Hypertrophic cardiomyopathy (HCM) is characterised by idiopathic cardiac enlargement and represents the most frequent cause of sudden cardiac death in athletes under the age of 35 years. Differentiation between physiological (ie, exercise-related) and pathological (ie, HCM-related) cardiac remodelling is challenging. In line with cardiac remodelling, vascular structure and function are altered following training, but little is known about peripheral vascular adaptations in HCM. We hypothesised that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Time to peak brachial diameter after cuff deflation was reported in one study (3). Shear rate parameters were reported in 15 studies (1,20,36,37,40,46,49,59), eight of which presented peak shear rate after cuff deflation (1,37,40,46) and seven presented area under the curve of shear rate until time of peak brachial diameter (20,36,49,59). Baseline brachial diameter ranged from 3.2 to 5.4 mm in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time to peak brachial diameter after cuff deflation was reported in one study (3). Shear rate parameters were reported in 15 studies (1,20,36,37,40,46,49,59), eight of which presented peak shear rate after cuff deflation (1,37,40,46) and seven presented area under the curve of shear rate until time of peak brachial diameter (20,36,49,59). Baseline brachial diameter ranged from 3.2 to 5.4 mm in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…As for the duration of blood flow occlusion, 23 studies used a 5-min period, whereas six studies reported periods between 4 and 5 min (1,23,27,44,50,56). Peak brachial diameter after cuff deflation (i.e., during hyperemia) was determined via continuous ultrasound scan in 20 studies (1,3,(12)(13)(14)20,27,36,40,49,50,59,60) and single time point(s) ultrasound scan in seven studies (23,29,32,(44)(45)(46)56), and one study did not report such information (37). Time to peak brachial diameter after cuff deflation was reported in one study (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on the effect of endurance training on wall thickness suggests that wall thickness is reduced with training both in the forearm and leg (90,372,373,427) although an increased arterial wall thickness in parallel with an increase in arterial diameter has been reported (389).…”
Section: Effects Of Training On Arterial Wall Thicknessmentioning
confidence: 99%
“…Post-contractile BOLD contrast has been used to characterize skeletal muscle function in healthy, sedentary, and active populations (13). Structural and functional changes in the microvasculature play a pivotal role in the pathogenesis of cardiovascular disease, hypertension, and diabetes (4,5). Therefore, muscle BOLD may be a powerful tool for measuring peripheral vascular function in individuals with peripheral arterial occlusive disease (6), obesity (7), and diabetes (7,8).…”
Section: Introductionmentioning
confidence: 99%